2020
DOI: 10.1002/jez.2398
|View full text |Cite
|
Sign up to set email alerts
|

The control of routine fish maneuvers: Connecting midline kinematics to turn outcomes

Abstract: Maneuverability is an important factor in determining an animal's ability to navigate its environment and succeed in predator–prey interactions. Although fish are capable of a wide range of maneuvers, most of the literature has focused on escape maneuvers while less attention has been paid to routine maneuvers, such as those used for habitat navigation. The quantitative relationships between body deformations and maneuver outcomes (displacement of the center of mass and change in trajectory) are fundamental to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…C-starts in live fish exhibit muscle activation patterns that are more akin to the C-start control scheme that we, and others (Jindong and Huosheng 2005, Su et al 2011, have encoded, wherein all the muscles activate simultaneously and deactivate sequentially (Jayne and Lauder 1993). However, in our observations of the kinematics of C-starts, we found that the patterns of developing and propagating curvature were similar regardless of the type of stimulus, though escape maneuvers were much higher intensity than routine maneuvers (Howe and Astley 2020). Interactions between the neuromuscular system, the material properties of the body, muscle physiology, and the forces imposed on the body by the water all likely work together to create the kinematic patterns we observe in live fish (Tytell et al 2011), it would make sense that combinations of similar factors could give rise to the kinematic patterns we observed in the C-start control scheme.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…C-starts in live fish exhibit muscle activation patterns that are more akin to the C-start control scheme that we, and others (Jindong and Huosheng 2005, Su et al 2011, have encoded, wherein all the muscles activate simultaneously and deactivate sequentially (Jayne and Lauder 1993). However, in our observations of the kinematics of C-starts, we found that the patterns of developing and propagating curvature were similar regardless of the type of stimulus, though escape maneuvers were much higher intensity than routine maneuvers (Howe and Astley 2020). Interactions between the neuromuscular system, the material properties of the body, muscle physiology, and the forces imposed on the body by the water all likely work together to create the kinematic patterns we observe in live fish (Tytell et al 2011), it would make sense that combinations of similar factors could give rise to the kinematic patterns we observed in the C-start control scheme.…”
Section: Discussionsupporting
confidence: 45%
“…The head was the longest body segment at 30% of the total length. The head in the robot is longer than the head we measured in live fish, but the amount of curvature we measured in this region on the fish's midline was low (figure 1(A), Howe and Astley (2020)). Active segments were the same length at 14% TL.…”
Section: Robot Constructionmentioning
confidence: 62%
See 3 more Smart Citations